Related factor in lamentation risk of low back pain on inpatient nurse - Lukmanulhakim, L; Awaludin, Andi Achmad (Universitas Aisyah Pringsewu, 2019)
Low back pain (LBP) is one of the musculoskeletal disorders caused by poor body activity. This study aims to determine the factors associated with the risk of LBP complaints of nurse in the ward at the Banten Provincial Hospital. The research method used was analytic observational through cross sectional approach. The research respondents were 34 nurses who were selected by using probability sampling with cluster sampling type. The measurement of age, work period, and BMI used respondent characteristics form, work posture measurement used RULA, and the measurement of LBP complaints used the LBP symptom questionnaire. The statistical test used the chi square test with a significant level 0.05. The test results of the relationship between individual characteristics and the risk of LBP complaints obtained age (p=0.677), work period (p=0.811), BMI (p=0.350), and the relationship between work posture and the risk of LBP complaints (p=0.001). Based on the results of research statistics, it was found that there was no significant relationship between age, work period, and BMI with the risk of LBP complaints and there was a relationship between work posture and the risk of LBP complaints. The researcher suggested that the nurse should pay attention to their work posture when conducting a nursing intervention. AbstrakLow back pain (LBP) merupakan salah satu gangguan muskuloskeletal yang disebabkan oleh aktivitas tubuh yang kurang baik. Penelitian ini bertujuan untuk mengetahui faktor-faktor yang berhubungan dengan Risiko keluhan LBP pada perawat Instalasi rawat inap RSUD Provinsi Banten. Metode penelitian yang digunakan adalah analitik observasional melalui pendekatan cross sectional. Responden penelitian sebanyak 34 perawat dengan menggunakan probability sampling dengan jenis cluster sampling. Pengukuran umur, masa kerja, dan IMT menggunakan lembar isi karakteristik responden, postur kerja menggunakan RULA dan pengukuran keluhan LBP dengan kuesioner gejala LBP. Uji statistik menggunkan uji chi square dengan tingkat signifikan 0,05. Hasil uji hubungan karakteristik individu dengan keluhan LBP menunjukan hasil umur (p=0,677), masa kerja (p=0,811), IMT (p=0,350), serta hubungan postur kerja dengan keluhan LBP (p=0,001). Berdasarkan hasil data statistik penelitian, tidak ada hubungan yang signifikan antara umur, masa kerja, IMT dengan risiko keluhan LBP dan ada hubungan antara postur kerja dengan keluhan LBP. Peneliti menyarankan agar perawat memperhatikan postur kerja pada saat melakukan intervensi keperawatan.